Regulation of Transcription by Hypoxia Requires a Multiprotein Complex That Includes Hypoxia-Inducible Factor 1, an Adjacent Transcription Factor, and p300/CREB Binding Protein - Ebert, Benjamin L. (American Society for Microbiology, 1998)
Molecular adaptation to hypoxia depends on the binding of hypoxia-inducible factor 1 (HIF-1) to cognate response elements in oxygen-regulated genes. In addition, adjacent sequences are required for hypoxia-inducible transcription. To investigate the mechanism of interaction between these cis-acting sequences, the multiprotein complex binding to the lactate dehydrogenase A (LDH-A) promoter was characterized. The involvement of HIF-1, CREB-1/ATF-1, and p300/CREB binding protein (CBP) was demonstrated by techniques documenting in vitro binding, in combination with transient transfections that test the in vivo functional importance of each protein. In both the LDH-A promoter and the erythropoietin 3′ enhancer, formation of multiprotein complexes was analyzed by using biotinylated probes encompassing functionally critical cis-acting sequences. Strong binding of p300/CBP required interactions with multiple DNA binding proteins. Thus, the necessity of transcription factor binding sites adjacent to a HIF-1 site for hypoxically inducible transcription may be due to the requirement of p300 to interact with multiple transcription factors for high-affinity binding and activation of transcription. Since it has been found to interact with a wide range of transcription factors, p300 is likely to play a similar role in other genes, mediating interactions between DNA binding proteins, thereby activating stimulus-specific and tissue-specific gene transcription.